Quantity Maxim Violation in Corbuzier Podcast Youtube Anies Menjawab - Rodiah, Huaini; Fatmawati, Fatmawati (Universitas Muria Kudus, 2022)
Tujuan penelitian ini yaitu untuk mengetahui pelanggaran maksim kuantitas serta alasan pelanggaran maksim tersebut pada program Corbuzier Podcast Anies Menjawab di Youtube. Peneliti menyertarakan alasan pelanggaran pada maksim kuantitas ini untuk memberitahukan bahwa pelanggaran pada maksim kuantitas tersebut terjadi bukan hanya kebetulan saja, tetapi adanya alasan tertentu sehingga terjadinya pelanggaran. Alasan pelanggaran pada maksim kuantitas digolongkan menjadi 5 kategori. Peneliti menggunakan metode analisis isi. Pendekatan dalam penelitian ini yaitu pendekatan kualitatif. Hasil penelitian ini dari 267 tuturan ditemukan 95 tuturan yang dilanggar. Dari 95 tuturan tersebut terdapat 49 tuturan yang melanggar maksim kuantitas dengan 5 kategori alasan pelanggarannya. The difference in the application of the principle of cooperation proposed by Grice with what happened in Indonesia causes violations of the principle of cooperation to occur frequently. This is what makes researchers interested in conducting research on violations of the Grice cooperation principle in the Corbuzier Podcast Anies Answering program on Youtube, especially on the maxim of quantity that is most often in the speech of this event. The source of data in this study is language activities that occur in the Corbuzier Podcast Anies Answers program on Youtube. The data in this study are all utterances that violate the cooperative principle spoken by Deddy and his guest stars. The purpose of this study is to find out the violation of the maxim of quantity and the reasons for the violation. The researcher includes the reasons for the violation of the maxim of quantity to inform that the violation of the maxim of quantity occurs not just by chance, but there are certain reasons that led to the violation. The researcher used content analysis method. The approach in this study is a qualitative approach. The results of this study from 267 utterances found 95 utterances that were violated. Of the 95 utterances, there are 49 utterances that violate the maxim of quantity with 5 categories of reasons for the violation. Violations of the maxim of quantity often occur in this program because this program is a question and answer program to get a lot of information that must be produced according to the needs and desires of the audience and the community. So that a lot of speech is redundant in providing information. This happened in general to fulfill the purpose of this event, which was made with the theme Anies Answering. Anies' answer is very much needed by the community, so Anies's speech often violates the maxim of quantity, because it provides clear information to the public.